High-Performance Cu-Based Liquid Thermocells Enabled by Thermosensitive Crystallization and Etched Carbon Cloth Electrode - Fang, Wei; Ou, Zeping; Wang, Yifan; Li, Zhe; Huang, Qian; Zhang, Pengchi; Li, Xinzhe; Zheng, Yujie; Hu, Lijun; Li, Chen; Ouyang, Jianyong; Sun, Kuan (Nano-Micro Letters, 2026)
Thermocells are garnering increasing attention as a promising thermoelectric technology for harvesting low-grade heat. However, their performance is often limited by the scarcity of high-performance redox couples that possess both high thermopower and rapid redox kinetics. This work addresses this challenge by leveraging our recently developed copper (I/II) (Cu+/Cu2+) redox couple. We significantly enhance the performance of Cu-based liquid thermocells by integrating a thermosensitive crystallization process with etched carbon cloth electrodes, achieving synergistic improvements in thermodynamic and kinetic performance. The thermosensitive crystallization process establishes a persistent Cu2+ concentration gradient, boosting the thermopower from 1.47 to 2.93 mV K−1. Moreover, the etched carbon cloth electrodes provide a larger electroactive surface area and demonstrate a higher current density. Consequently, the optimized Cu+/Cu2+ system achieved an exceptional normalized power density Pmax (ΔT)−2 of 3.97 mW m‒2 K−2. A thermocell module comprised of 20 cells directly power various electronic devices at a temperature difference of 40 K. This work successfully exhibits potential of Cu+/Cu2+ redox couple in thermoelectric conversion and introduces a valuable redox couple for high-performance thermocells. Highlights: 1 A novel Cu+/Cu2+ redox couple was introduced to enable a thermosensitive crystallization process, significantly enhancing thermopower from 1.47 to 2.93 mV K‒1. 2 A readily fabricated etched carbon cloth electrode offered an enlarged electroactive surface area, demonstrating superior current density through improved kinetics. 3 The optimized Cu+/Cu2+ system, achieved through synergistic enhancements in thermodynamic and kinetic performance, delivered an outstanding normalized power density Pmax (ΔT)‒2 of 3.97 mW m‒2 K‒2.